Geography, physical and human environments - Campbell, Calum; Geddes, Ian (Dynamic learning, 2019)
Exam Board: SQA Level: Higher Subject: Geography First Teaching: August 2018 First Exam: June 2019 A fully updated, full colour textbook for areas 1 and 2 of SQA Higher Geography, providing a complete guide to all components of the Physical and Human elements of the course. - Blends theoretical content and processes with detailed guidance on practical aspects - Offers regular 'What you need to know' sections, consolidation questions, reflection tasks, key words and definitions, plus Assignment links and ideas for the non-examination sections of the course - Geographical and Mapping Skills are explained and illustrated throughout the text, which also provides: - exam style questions in every chapter - new, contemporary case studies and exemplars - fresh and inspirational examination of well-known geographical themes A companion volume, Higher Geography: Global Issues, provides material for area 3 of the Higher course.